Ethnobotany of Rubiaceae Family Plants Used As Traditional Medicine in Tanjung Gusta Village Sunggal District, Deli Serdang Regency - Siregar, Rivahni; Idris, M.; Rahmadina, Rahmadina (Universitas Labuhanbatu, 2024)
Medicinal plants are all types of plants that are known to contain compounds that are useful and efficacious to prevent, alleviate or cure a disease. Rubiaceae is one of the flowering plant tribes. This study aims to determine the type of plant, how to use, and the value of ICS (Index Culture Significance) on plants of the Rubiaceae family in Tanjung Gusta Village, Sunggal District, Deli Serdang Regency, which was conducted in May - July 2022. The research method used a descriptive survey conducted by means of field surveys and interviews. The results showed that the types of plants of the Rubiaceae family used as traditional medicine in Tanjung Gusta village are noni (Morinda citrifolia L.), asoka flower (Ixora coccinea), gambier (Uncaria acida), quinine (Cinchona pubeschens), cat's claw (Uncaria tomentosa). How to use noni by squeezing the juice, for asoka flowers by brewing, for gambier by mashing, for quinine which is used is the skin, and for cat's claw by boiling. The highest ICS value is obtained from the noni plant (Morinda citrifolia L) with a value of 24 and the lowest ICS value is obtained from the Asoka plant (Ixora coccinea) and also the quinine plant (Cinchona pubeschens) which both have the lowest ICS value with a value of 12.